The Use of Portfolio Assessment in Process-Based Academic Essay Writing Instruction - Tyas, Peptia Asrining (Fakultas Ilmu Budaya, Universitas Brawijaya, 2012)
Although the concept of process-based approach in writing instruction in the teaching of EFL becomes popular in the recent years, many English teachers still used conventional method in teaching writing that only concern about the final product with perfect grammar and vocabulary. Thus, many educators suggested the use of a process based approach in teaching writing which is consists of various activities, namely prewriting, drafting, responding, revising, editing, assessing, post-writing, and reflection. Those activities can give students opportunities to improve their writing composition, perhaps motivate them to be a better writer, and of course train them to have critical thinking in order to make optimal interaction of teacherstudent and among students. Keywords: writing process-based approach, portfolio assessment, and process-product assessments.